Biomass sugars for non-fuel applications - Murzin, Dmitry, 1963-; Simakova, Olga A. (Royal Society of Chemistry, 2015)
Biomass-derived sugars provide a rich, renewable feedstock for a diverse range of chemicals, making them a promising and feasible source for the sustainable manufacture of a variety of valuable products. Exploring green sugar-based technologies beyond their applications in fuels, this book provides an overview of sugar-based technologies, describing their challenges and opportunities. It covers transformations of sugars into green chemicals in pharmaceuticals, biodegradable polymers and surfactants. A special chapter is dedicated to the conversion of biomass into sugars, which is a crucial step in the sustainable utilization of sugars. The book is a valuable resource for chemists and chemical engineers working to develop greener synthetic routes to chemicals and pharmaceuticals.
Includes index.
Keywords: Biomass chemicals.; Green chemistry.; elektronické knihy; electronic books